THE EFFECT OF GROUP TYPE COOPERATIVE LEARNING MODELS INVESTIGATION OF CONCEPTUAL KNOWLEDGE STUDENTS ON BUSINESS AND ENERGY MATERIALS - Lasria Lestari Situmorang; Mara Bangun Harahap; Indah Cahyani (UNIVERSITAS NEGERI MEDAN, 2019)
This study aims to determine the effect of cooperative learning model type of group investigation on student’s conceptual knowledge and activities in the subject work and energy. This research is a quasi-experiment using two-group pretest-posttest design. The study sample consisted of two classes, namely the XI MIA-1 class as the experimental class and the XI MIA-3 class as the control of which amounted to 32 students, the sampling be done with random sampling technique. The instrument used was a test of learning outcomes in the form of students conceptual knowledge in the form of 8 essay test. In the experimental class the average activity of students in the three meetings, are 60%, 72% and 87%. From the data obtained, there is evidence of the effect of group investigation models in improving learning activity on work and energy topic in XI Senior High School 10 Medan. The hypothesis with t-test shows the result there was a significant influence of cooperative learning model type group investigation to conceptual knowledge student subject of work and energy in class XI SMA Negeri 10 Medan T.P 2018/2019. Keywords: cooperative learning type group investigation, activities, conceptual knowledge